PENYULUHAN PREEKLAMPSI PADA WANITA HAMIL DI PUSKESMAS SUKODONO SIDOARJO - Alfina Aisatus Saadah; Mohammad Yusuf Setiawan; Diah Wijayanti Sutha (Jurnal AbdiMas Nusa Mandiri, 2025)
Preeclampsia accounts for approximately 58.1% of the 585,000 maternal deaths that occur worldwide each year during pregnancy and childbirth, while eclampsia ranks as the second leading cause of maternal death, accounting for 26.9% of cases in 2012 and 27.1% in 2013. This community service project aimed to increase knowledge and awareness regarding preeclampsia among health cadres at the Sukodono Sidoarjo Public Health Center. The activity was carried out through counseling sessions as the main method of community education. The target participants were posyandu cadres who play a vital role in maternal and child health promotion. Based on data obtained from pre-test and post-test questionnaires, participants’ comprehension levels prior to counseling were 22% in the good category, 61% sufficient, and 17% poor. After the counseling, the results showed a significant improvement, with 76% of participants in the good category, 24% sufficient, and 0% poor. These findings indicate that counseling activities effectively improved cadres’ understanding of preeclampsia. Strengthening cadre knowledge through continuous education is essential to help reduce maternal and infant mortality rates.